2013
DOI: 10.11609/jott.o3096.210
|View full text |Cite
|
Sign up to set email alerts
|

Avian collision threat assessment at ‘Bhambarwadi Wind Farm Plateau’ in northern Western Ghats, India.

Abstract: Abstract:To address the shortage of power in India, wind energy is increasingly harnessed as an alternate and renewable energy source. There is a rapid increase in the number of wind farms at suitable sites all over the country. Some of the key sites with optimal wind velocities are the plateaus on the Western Ghats -a global hotspot of biological diversity. The rocky plateaus on the Western Ghats are terrestrial habitat islands facing extreme micro-environmental conditions; however, scanty information is avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…India's government is working to provide electric power to all households and, although this goal has not yet been achieved, power is currently being provided to many rural centers (Modi 2005) and new power-generation facilities are being developed (Pande et al 2013). The poles used to deliver this power typically operate at 11 or 33 kilovolts (kV) of alternating current and the power lines cross undeveloped landscapes occupied by numerous avian species.…”
Section: Electrocuciones De Aves En El Oeste De Rajasthan Indiamentioning
confidence: 99%
“…India's government is working to provide electric power to all households and, although this goal has not yet been achieved, power is currently being provided to many rural centers (Modi 2005) and new power-generation facilities are being developed (Pande et al 2013). The poles used to deliver this power typically operate at 11 or 33 kilovolts (kV) of alternating current and the power lines cross undeveloped landscapes occupied by numerous avian species.…”
Section: Electrocuciones De Aves En El Oeste De Rajasthan Indiamentioning
confidence: 99%
“…Several authors from various parts of the world have discussed the wind farm mortality of bats (Barclay et al 2007;Miller 2008;Cryan & Barclay 2009;Graham & Hudak 2011;Jameson & Wills 2012). However, despite the large number of wind farms found in India, their impact on birds and bats has been sporadically reported, except for the very recent report of Pande et al (2013). In this paper we report mortality of bats due to collision with the wind turbines in Kutch District, Gujarat.…”
mentioning
confidence: 78%
“…There is a large wind farm near the type locality at Chalkewadi and the other localities are also potential wind farm sites. Pande et al (2013) have discussed threat of wind farms to avifauna wherein they discuss the windmill erection activity to be a measured threat to general diversity as well. Recently, Dahanukar et al (2013) reported the presence of chytrid fungal infection in morphologically identified R. bombayensis from Taleghar, which should be attributed to the R. ghatei sp.…”
Section: Discussionmentioning
confidence: 99%